ANALISIS DETERMINASI INNOVATIVE WORK BEHAVIOR DI YAYASAN TP 45 - DANANJAYA, IDA BAGUS GEDE; SANJAYA, IDA BAGUS; SAPUTRA, UPAYANA WIGUNA EKA; FAKRUROZI, RIFQI NUR; SITAWATI, ANAK AGUNG RAKA; SUMETRI, NI WAYAN (GANEC SWARA, 2024)
This study aims to determine the determination of Innovative work behavior on Employees and Teachers at the TP 45 Foundation. The theory used is Innovative work behavior, Psychological Capital and Psychological Empowerment. This type of research uses quantitative methods. The sample for this research is all employees and teachers who work at the TP 45 Foundation. The data collection method used is the sampling technique in this study using probability sampling with saturated sampling technique, where the sample selection has certain criteria. The data analysis technique used in this study is to use structural equation modeling (SEM) or structural equation models using the partial least squares (PLS) approach. Partial Least Square (PLS) is used to determine the complexity of the relationship between latent variables and their indicators. The results of this research show that Psychological Empowerment has a positive and significant effect on innovative work behavior. Psychological Capital has a positive and significant effect on innovative work behavior. Psychological Empowerment has a positive and significant effect on Psychological Capital Psychological Capital partially mediates the effect of Psychological Empowerment on innovative work behavior